Histomorphological Studies of the Proventriculus In Post-Hatch Guinea fowl (Numida meleagris) - Selvan, P Senthamil; Ushakumary, S; Ramesh, Geetha (Indian Journal of Veterinary Anatomy, 2018)
The mucus membrane of proventriculus of guinea fowl had all the four tunics namely, tunica mucosa, tunica submucosa, tunica muscularis and tunica serosa. The tunica mucosa showed mucosal folds. The lamina propria contained simple tubular glands and a single distinct longitudinal layer of smooth muscle formed the muscularis mucosa. Well developed submucosa contained compound tubulo-alveolar glands.. Endocrine cells were more and present among the glandular cells of the submucosal glands. Tunica muscularis had an inner longitudinal, middle circular and outer thin longitudinal layer and tunica serosa was thin.